2015
DOI: 10.1371/journal.pone.0118829
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of TP53 Codon 72 and MDM2 SNP 309 Polymorphisms in Pancreatic Ductal Adenocarcinoma

Abstract: Single-nucleotide polymorphisms (SNPs) of TP53 (codon 72, rs1042522) and MDM2 promoter (SNP 309, rs2279744) have been associated with risk for various human cancers. However, studies analyzing these polymorphisms in pancreatic ductal adenocarcinoma (PDAC) are lacking. We investigated TP53 codon 72 and MDM2 SNP 309 polymorphisms in 32 patients with PDAC, 16 patients with chronic pancreatitis (CP), and 32 normal controls, using formalin-fixed paraffin-embedded tissue. We also examined TP53 and MDM2 protein immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…However, they found patients with MDM2 GG genotype had shorter total life expectancy compared to those with other (TG, TT) genotypes (40). Another study by Chua et al reported MDM2 TT genotype was associated with lung cancer in non-smoking women in a Chinese population (41). A similar study in the same population showed the G allele was associated with increased risk of cancer; however, early age of onset was found to be associated with the TT genotype (42).…”
Section: Discussionmentioning
confidence: 93%
“…However, they found patients with MDM2 GG genotype had shorter total life expectancy compared to those with other (TG, TT) genotypes (40). Another study by Chua et al reported MDM2 TT genotype was associated with lung cancer in non-smoking women in a Chinese population (41). A similar study in the same population showed the G allele was associated with increased risk of cancer; however, early age of onset was found to be associated with the TT genotype (42).…”
Section: Discussionmentioning
confidence: 93%
“…The best explanation of this came from the knowledge of different polymorphic variants of various genes; particularly those involved in cell cycle control and DNA repair mechanism, and their frequency varies among different population. p53 is one of the most studied proteins that plays fundamental role in regulating basic cellular function and because of this, it is an important target protein to study different polymorphic variants of p53 for their association with various diseases including colon carcinomas [10,[12][13][14]27]. A SNP in MDM2 (SNPT309G), a negative regulator of p53, alone or in combination with p53 has been reported to associate with different carcinomas and progression of disease [14,18,22,23,25,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…p53 is one of the most studied proteins that plays fundamental role in regulating basic cellular function and because of this, it is an important target protein to study different polymorphic variants of p53 for their association with various diseases including colon carcinomas [10,[12][13][14]27]. A SNP in MDM2 (SNPT309G), a negative regulator of p53, alone or in combination with p53 has been reported to associate with different carcinomas and progression of disease [14,18,22,23,25,[27][28][29][30]. Over the last decade, studies have reported the role of p53 R72P and MDM2 T309G polymorphisms as risk factor for colorectal carcinoma [14,15,19,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, affecting the AURORA signaling pathway by influencing TP53 and MDM2 can indirectly lead to changes in the occurrence and progression of PDAC. 85 In the past, many signaling pathways, nutrients and natural products interacted with pathways involved in TP53 and drug resistance. 86 TP53-positive chronic pancreatitis is considered inefficient in inducing carcinogenesis.…”
Section: Tp53mentioning
confidence: 99%